1985
DOI: 10.1111/j.1151-2916.1985.tb15320.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Reactions of Pyrophyllite Studied by High‐Resolution Solid‐state 27Al and 29Si Nuclear Magnetic Resonance Spectroscopy

Abstract: Water is lost in two overlapping steps from well-crystallized pyrophyllite from Coromandel, New Zealand. The pyrophyllite structure survives the loss of the first 30% of the total water content, but the loss of a further 60% water in the second step results in the formation of pyrophyllite dehydroxylate, with corresponding changes in both the 29Si and 27AI solid-state NMR spectra. Detailed analysis of the z9Si chemical shift of the dehydroxylate has allowed the silicate layer structure of this phase to be refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 13 publications
4
40
0
2
Order By: Relevance
“…After dehydroxylation, but prior to recrystallization, the amount of A1 visible was small and resulted in poor signal-to-noise, but peaks appeared to be present at about 37 and 59 ppm ( Figure 3J). Similar results were found for both dehydroxylated pyrophyllite and metakaolinite by MacKenzie et al (1985aMacKenzie et al ( , 1985b, who suggested that these two peaks represented A1 in slightly different tetrahedral environments, although the peak at 37 ppm could possibly have been due to a more regular 5-coordinated A1 site (Alemany and Kirker, 1986). The separation of these sites was lost on recrystallization of the sample ( Figure 3K), which was accompanied by a further increase in the proportion of detectable tetrahedral AI ( Figure 4B) and a change in the octahedral chemical shift to -15 ppm ( Figure 3L).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…After dehydroxylation, but prior to recrystallization, the amount of A1 visible was small and resulted in poor signal-to-noise, but peaks appeared to be present at about 37 and 59 ppm ( Figure 3J). Similar results were found for both dehydroxylated pyrophyllite and metakaolinite by MacKenzie et al (1985aMacKenzie et al ( , 1985b, who suggested that these two peaks represented A1 in slightly different tetrahedral environments, although the peak at 37 ppm could possibly have been due to a more regular 5-coordinated A1 site (Alemany and Kirker, 1986). The separation of these sites was lost on recrystallization of the sample ( Figure 3K), which was accompanied by a further increase in the proportion of detectable tetrahedral AI ( Figure 4B) and a change in the octahedral chemical shift to -15 ppm ( Figure 3L).…”
Section: Resultssupporting
confidence: 85%
“…Calibration of the integrated peak intensities with respect to the intensity produced by a known amount of A1 in an external standard of ot-A120 3 indicated that the NMR experiment detected all the A1 present in the unheated sample, but that the loss of both hydration and hydroxyl water decreased the amount of A1 detected in the heated samples (Figure 4). Recrystallization at higher temperatures only slightly improved the A1 detection level, consistent with the dehydroxylation behavior of other hydrated aluminosilicates studied by solid-state NMR (MacKenzie et aL, 1985a(MacKenzie et aL, , 1985bBrown et al, 1987).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…One of more investigated solid alumosilicate under highly alkaline conditions is the 1:1 layer lattice alumosilicate mineral -kaolinite [6].Although the mainly used in the preparation of 1:1 layer lattice alumosilicates, i.e.,geopolymers, it is also of interest 2:1minerals such as 2:1 analogue of kaolinite -pyrophillite with unitstructure Al 2 AlSi 3 O 10 (OH) 2 , in which the octahedral Al-O sheet isenclosed above and below by two tetrahedral Si-O sheets to form a repeating unit [7]. It is shown that attempts to produce fully reacted alumosilicategeopolymers from the crystalline 2:1 lattice mineral, pyrophillite, was unsuccessful.…”
Section: Introductionmentioning
confidence: 99%